2022
DOI: 10.18844/wjet.v14i6.7131
|View full text |Cite
|
Sign up to set email alerts
|

Educational benefits of hackathon: A systematic literature review

Abstract: Hackathons are said to promote a variety of innovative ideas and can be traced back to the idea of problem-solving. There is little research on the use of hackathons in classes to meet course-level learning objectives, despite the emphasis given to its advantages in other human efforts. By conducting a systematic literature review (SLR), this study uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement criteria to better understand the advantages of hackathons in educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Therefore, our student-centred teaching intervention aimed to achieve its objectives by inviting penultimate-year engineering and computer science students to participate in a 3-day hackathon to raise empathy, education and awareness around four UN SDGs (depicted in the concept image shown in Figure 1. Evidence suggests that these programmes offer students an opportunity to forge relationships with new staff/students and to gain new skills [21]. The term "hackathon" combines the words "hack" and "marathon" and denotes an extended, focused time spent developing a project [22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our student-centred teaching intervention aimed to achieve its objectives by inviting penultimate-year engineering and computer science students to participate in a 3-day hackathon to raise empathy, education and awareness around four UN SDGs (depicted in the concept image shown in Figure 1. Evidence suggests that these programmes offer students an opportunity to forge relationships with new staff/students and to gain new skills [21]. The term "hackathon" combines the words "hack" and "marathon" and denotes an extended, focused time spent developing a project [22].…”
Section: Introductionmentioning
confidence: 99%
“…One potential method for hands-on AI education popular across many fields of science and engineering is the "hackathon" and related "datathon", which are short competitions in which teams of students work together to create new solutions to domain-specific challenges through leveraging real-world data and algorithms. Oyetade et al [4] offer a scoping review of hackathons and found that such events help students learn both technical and soft skills, and argue that hackathon-based pedagogies be incorporated in classroom environments. Silver et al [5] describe a hackathon event for current attendings in clinical practice, and found that study participants were better equipped to accelerate specialty-focused innovation after the hackathon.…”
Section: Introductionmentioning
confidence: 99%
“…The participants in the hackathon can be a diverse range of individuals according to the purpose and topic of the hackathon and having experience and knowledge in that field. 1 Hackathons can take place in physical locations, such as conference centers or university campuses, or be held virtually, allowing participants from different locations to join remotely. The event structure requires participants to engage in team formation, problem identification, and preparation for the presentation and demonstration of their solution which aligns with the Double Diamond design process.…”
mentioning
confidence: 99%
“…Deliver is closely linked with the Develop phase, and often observed rotation between the two phases to synthesize the final design in the design process throughout the hackathon. 1 Hackathons provide a solution-oriented environment for participants to collaborate, learn from others, and network with like-minded individuals. These events offer opportunities for teamwork, creativity, critical thinking, and fostering a sense of innovation among participants.…”
mentioning
confidence: 99%
See 1 more Smart Citation